1996
DOI: 10.1161/01.str.27.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Craniotomy for Intracranial Aneurysm and Subarachnoid Hemorrhage

Abstract: Whereas mortality is higher for the older age group, quality of life scores appear acceptable for those who survive. Even though the hospital costs of treating elderly patients for SAH may be higher than those for younger patients, this should not be used to justify withholding care from the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 17 publications
4
17
1
Order By: Relevance
“…21 It has been reported that the average craniotomy procedure itself costs $15,867 at high-volume centers. 21 Nevertheless, taken with findings that have demonstrated that quality-of-life scores remain high for elderly survivors after undergoing craniotomy for intracranial hemorrhage, 30 our findings suggest that with some added care, patients over the age of 80 may recover as successfully as younger patients and that these costs may be warranted among this population. Our findings also demonstrated that age greater than 80 years predicted the need for rehabilitation after undergoing craniotomy.…”
Section: (Continued)supporting
confidence: 64%
“…21 It has been reported that the average craniotomy procedure itself costs $15,867 at high-volume centers. 21 Nevertheless, taken with findings that have demonstrated that quality-of-life scores remain high for elderly survivors after undergoing craniotomy for intracranial hemorrhage, 30 our findings suggest that with some added care, patients over the age of 80 may recover as successfully as younger patients and that these costs may be warranted among this population. Our findings also demonstrated that age greater than 80 years predicted the need for rehabilitation after undergoing craniotomy.…”
Section: (Continued)supporting
confidence: 64%
“…The cost of treating aneurysmal SAH has been reported to increase with age 30 and clinical grade on admission. 31 With decreasing healthcare budgets and a constantly aging population, priorities must be made to ensure that money is spent in the best possible manner.…”
Section: Cost-effectiveness and Ethicsmentioning
confidence: 99%
“…In many developed countries, SAH after of 70 years of age has been a frequent pathology. 1,2,15,16,21,23,30,32,33 Some authors believe that there is not a persistent increase of rupture risk. They argue that a maximum level is reached by the age of 70 years, and then a decrease is expected.…”
Section: Discussionmentioning
confidence: 99%